Formation of nano-fibrils from the A, B and C variants of bovine β-lactoglobulin. (February 2015) - Dave, Anant C.; Loveday, Simon M.; Anema, Skelte G.; Jameson, Geoffrey B.; Singh, Harjinder
Abstract: This study investigated the self-assembly of purified β-lactoglobulin (β-Lg) genetic variants A, B and C into amyloid-like fibrils. β-Lg solutions (1%, w/v) were heated at 80 °C and pH 2 and were analysed for the presence of fibrils using the thioflavin T assay. Reducing sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) was used to follow heat-induced acid hydrolysis of β-Lg monomers. Fibrils separated from heated solutions were characterised by SDS-PAGE and transmission electron microscopy. The substitution of amino acid residues in β-Lg variants A, B and C did not significantly affect the kinetics of acid hydrolysis, self-assembly kinetics, or the morphology of the fibrils. The fibrils from β-Lg A, B and C were, however, slightly different in peptide compositions. These differences may be explained on the basis of amino acid substitutions, in particular the Asp64 of β-Lg A that is Gly in variants B and C.